Comparative analysis of the antibacterial activity of Silver nanoparticles synthesized from leaf extracts of Ocimum sanctum, Coriandrum sativum, Hemidesmus indicus, and Tinospora cordifolia - Golani, Mahima; Parnaik, Divya; Phanse, Nandini (Brazilian Journal of Science, 2024)
The synthesis of metal nanoparticles using biological resources, such as plant leaves, offers a green, cost-effective, and eco-friendly approach. In this study, 1 mM Silver nitrate solution was mixed with freshly prepared aqueous leaf extracts of each medicinal plant like, “Tulsi (Ocimum sanctum), Coriander (Coriandrum sativum), Anantmul (Hemidesmus indicus) and Giloy (Tinospora cordifolia)” in 1:4 ratios. The mixtures were then incubated at 75 °C for 25 min, forming Silver nanoparticles giving a deep brown color to the solution with Silver in a reduced colloidal form. Laser diffraction and UV-Vis spectroscopy further confirmed the synthesis, with the absorption peak for the nanoparticles observed between 419-438 nm. The antibacterial activity of the synthesized nanoparticles was tested against Gram-positive pathogens, including Staphylococcus aureus and Staphylococcus argenteus, as well as Gram-negative bacteria like Escherichia coli and Salmonella typhi. Comparative analysis showed that nanoparticles synthesized from Tulsi, Coriander, and Giloy extracts demonstrated superior antibacterial efficacy, highlighting their potential for use in biomedical and industrial applications such as wound healing, medical devices, and water purification.